Genetic parameters and trends for litter size in Black Slavonian pigs - Luković Z.; Karolyi D.; Klišanić V.; Mahnet Z.; Gantner V.; Škorput D. (7th International Symposium on the Mediterranean Pig, 2012)
Genetic progress in litter size in local pig breeds is limited mainly due to low heritability and inbreeding depression. After increase of population size of Black Slavonian (BS) pig breed in recent years, there is opportunity to renew a breeding programme including some new breeding goals related to litter size. Aim of study was to determine genetic parameters for litter size in BS pigs. Litter size was presented as number of piglets born alive (NBA) and number of piglets weaned (NW). Genetic parameters were estimated using a univariate repeatability models. Fixed part of the model included breeding organization, birth number, farrowing season and service sire as class effects. Random part of the model included direct additive genetic effect and permanent environmental effect. Litter size records proceeded from 5792 litters from 1817 sows. The complete pedigree file contained 1862 triads (animal-sire-dam). Heritability estimates for NBA and NW were lower than average values of 0.10 - 0.20, and ranged for both traits between 0.04 and 0.08. Implementation of some others models in breeding scheme (particularly multivariate and random regression models) requires availability of large set of reproductive traits for this local breed.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)